To solve the equation \( \frac{y}{7} - 3 = 39 \), Beejal can follow these steps:
-
As a first step, he starts by adding 3 to both sides of the equation. This will give him: \[ \frac{y}{7} = 39 + 3 \] which simplifies to: \[ \frac{y}{7} = 42 \]
-
Then, he continues by multiplying both sides by 7. This will give him: \[ y = 42 \times 7 \] which simplifies to: \[ y = 294 \]
So, the complete answer is: Beejal starts by adding 3 to both sides of the equation, and then continues by multiplying by 7 on each side.